2016
DOI: 10.1016/j.ecolind.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and uncertainty analyses of grassland biomass in Northern China: Comparison of multiple remote sensing data sources and modeling approaches

Abstract: a b s t r a c tAccurate estimation of grassland biomass and its dynamics are crucial not only for the biogeochemical dynamics of terrestrial ecosystems, but also for the sustainable use of grassland resources. However, estimations of grassland biomass on large spatial scale usually suffer from large variability and mostly lack quantitative uncertainty analyses. In this study, the spatial grassland biomass estimation and its uncertainty were assessed based on 265 field measurements and remote sensing data acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…The MODIS‐derived α value with an AGB model of [ f AGB = α × NDVI + β] for the grasslands was 839.9 g/m 2 (Xue et al, ) or 864.36 g/m 2 (Li et al, ) for the central IMAR, 638.19 g/m 2 (Xu et al, ) or 680.15 g/m 2 (Gao et al, ) for the western IMAR, and 1,156.72 (Li et al, ) or 1,161.13 g/m 2 (Xu et al, ) for the eastern IMAR. However, all of these models carried low R 2 values (e.g., 0.39 in Xu et al, ; 0.60 in Jia et al, for northern China), suggesting that large uncertainties existed in predicting AGB from these models. When the above model for northern China was used to estimate the grassland AGB in IMAR with α = 220.98 g/m 2 (Jia et al, ), the regional average would be significantly underestimated, as we found that the M scalar for the same region was 253.62 g/m 2 .…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The MODIS‐derived α value with an AGB model of [ f AGB = α × NDVI + β] for the grasslands was 839.9 g/m 2 (Xue et al, ) or 864.36 g/m 2 (Li et al, ) for the central IMAR, 638.19 g/m 2 (Xu et al, ) or 680.15 g/m 2 (Gao et al, ) for the western IMAR, and 1,156.72 (Li et al, ) or 1,161.13 g/m 2 (Xu et al, ) for the eastern IMAR. However, all of these models carried low R 2 values (e.g., 0.39 in Xu et al, ; 0.60 in Jia et al, for northern China), suggesting that large uncertainties existed in predicting AGB from these models. When the above model for northern China was used to estimate the grassland AGB in IMAR with α = 220.98 g/m 2 (Jia et al, ), the regional average would be significantly underestimated, as we found that the M scalar for the same region was 253.62 g/m 2 .…”
Section: Discussionmentioning
confidence: 95%
“…However, all of these models carried low R 2 values (e.g., 0.39 in Xu et al, ; 0.60 in Jia et al, for northern China), suggesting that large uncertainties existed in predicting AGB from these models. When the above model for northern China was used to estimate the grassland AGB in IMAR with α = 220.98 g/m 2 (Jia et al, ), the regional average would be significantly underestimated, as we found that the M scalar for the same region was 253.62 g/m 2 . More importantly, the M scalar across the IMAR grasslands varied substantially, ranging from 2 g/m 2 to 1,470 g/m 2 (Figure a).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations